Diagnóstico de acidentes ocupacionais em um hospital veterinário universitário do sul do Brasil - Rodrigues, Daniele (2022)
Studies show that the risk of accidents and the accident rate in the veterinary environment has been higher, compared to other professions. Veterinary hospitals and clinics offer the same risks inherent to the area of human health, however research in the scope of occupational health of the public service and specific statistics in the area of the veterinary environment are still scarce. Given this scenario, it was necessary to investigate the occurrences of occupational accidents and what risks workers and students at the University Veterinary Hospital (HVU) of the Federal University of Santa Maria (UFSM) are exposed to. For this, a consultation was carried out on the work routine, occupational health and occurrence of accidents, with the employees of this veterinary hospital, through a questionnaire with 31 questions, prepared by the authors, addressing questions about age, gender, time of living in the place. of work, sleep quality and satisfaction with work, hygiene and work habits, physical or mental discomfort, knowledge of specific regulations, exposure to risks, situations of accidents with biological, chemical, sharps, involving patients, presence of feeling of impotence in the face of animal suffering, accident records and changes in posture at work. We included in our research 55 TechnicalAdministrative Education (TAE) workers, 12 outsourced workers and 25 professors stationed at the study site, for manuscript I. For manuscript II, we sent the questionnaire to seven associations of undergraduate veterinary classes, enrolled from the fifth semester (period that start practices within the hospital) until the 10th semester, for 42 students of the Postgraduate Program in Veterinary Medicine (whose supervisors are assigned to the veterinary hospital) and for 29 students of the Residency Program in the Professional Health Area, corresponding to the areas of concentration: Small Animal Medical Clinic, Clinical Pathology, Imaging Diagnosis, Ruminant Clinic, Veterinary Surgery and Veterinary Anesthesiology. Our results among the different workers demonstrate that the knowledge of specific regulations for the health environment was greater in the group of workers who received training. The needle disposal behavior is related to accident claims involving sharps for administrative technicians. Accidents that directly involved patients, accidents involving biological secretions and risk of exposure to ionizing radiation were the ones with the highest percentage for statements among employees, although there were no statements among outsourced workers. Physical or verbal aggression was reported in all groups, as well as the search for specialized care to treat discomforts or injuries related to work at the veterinary hospital. The lack of knowledge about the conduct in carrying out accident records was the most cited reason for the lack of it. The results found for the students reveal that the habit of hand hygiene is present for 43.9% of the students, the use of personal protective equipment for 48.3%. The Regulatory Norm 32 is known by 39.4%, accidents with sharps was stated by 76.1%, with an association between these variables only in the residence group. Accidents with biological materials occurred with 63.9%, 80.5% reported accidents involving patients and the possibility of exposure to ionizing radiation by 73.2% of students. The occurrence of zoonoses was found to be higher in graduate studies at 13.0%, as well as accidents with chemicals at 34.8%. The female gender is predominant in the three groups, totaling 69.3%. Physical or mental discomfort was reported by 43.9% of the students, with anxiety being the most frequent complaint. Accident records were made by only 9.7% of students, however 69.3% claim to change their attitude towards activities. We believe that this work is a stimulus to give greater visibility to the veterinary hospital environment, which lacks rules and regulations for practices that involve specific situations in this work environment, as well as a specific accident notification system.